Language Assessment for Immigration: A Review of Validation Research Over the Last Two Decades - Yao, Don; Wallace, Matthew P. (Frontiers in Psychology, 2021)
The current paper critically reviewed 11 validation studies on language assessment for immigration over the last two decades to identify what has been focused on and what has been overlooked in the empirical research and to discuss current research interests and future research trends. Bachman and Palmer’s (2010) Assessment Use Argument (AUA) framework, comprising four inferences (i.e., assessment records, interpretations, decisions, and consequences), was adopted to collect and examine evidence of test validity. Results showed the consequences inference received the most investigations focusing on immigration-seekers’ and policymakers’ perceptions on test consequences, while the decisions inference was the least probed stressing immigration-seekers’ attitude towards the impartiality of decision-making. It is recommended that further studies could explore more kinds of stakeholders (e.g., test developers) in terms of their perceptions on the test and investigate more about the fairness of decision-making based on test scores. Additionally, the current AUA framework includes only positive and negative consequences that an assessment may engender but does not take compounded consequences into account. It is suggested that further research could enrich the framework. The paper sheds some light on the field of language assessment for immigration and brings about theoretical, practical, and political implications for different kinds of stakeholders (e.g., researchers, test developers, and policymakers).